Inequality in the Impact of the Coronavirus Shock: Evidence from Real Time Surveys - Abi Adams-Prassl; Teodora Boneva; Marta Golin; Christopher Rauh (Institute of Labor Economics (IZA), 2020)
We present real time survey evidence from the UK, US and Germany showing that the labor market impacts of COVID-19 differ considerably across countries. Employees in Germany, which has a well-established short-time work scheme, are substantially less likely to be affected by the crisis. Within countries, the impacts are highly unequal and exacerbate existing inequalities. Workers in alternative work arrangements and in occupations in which only a small share of tasks can be done from home are more likely to have reduced their hours, lost their jobs and suffered falls in earnings. Less educated workers and women are more affected by the crisis.
Keywords: J21; J22; J24; J33; J63; 330; recessions; inequality; labor market; unemployment; Coronavirus; COVID-19